Ethnographic conversations with Wittfogel’s ghost: an introduction - Ley, Lukas; Krause, Franz (Environment and planning. C, Politics and space, 2019)
This theme issue re-engages the ghost of Wittfogel in ethnographically grounded conversations around the imbrication of water, power, and infrastructure. It examines social and political relations in ways that take their tensions and correspondences with water seriously, as Wittfogel did half a century ago, but in a less monolithic and totalizing manner. Instead, the contributions pay attention to the situated, partial, multiple, and open-ended encounters that (un)make these links. Together, the papers collected in this theme issue build a critical conversation around the role of water in configuring and reproducing power. Its major threads are the construction of authority through water, the social complexity of water relations, and the interrelationships between water, infrastructure, and political rule.